Implementation Of Problem Based Learning Model In Improving Learning Outcomes In Ipas Grade IV Elementary School - Reftiani Wulandari; Atri Widowati; Destrinelli Destrinelli (International Journal of Science and Environment (IJSE), 2025)
The aim of this research is to find out how to apply the Problem Based Learning learning model in improving student learning outcomes in elementary school science learning. The research method used is a classroom action research method that uses the development model by Kemmis and Mc. Taggart. The subjects of this research were 32 class IV students at SDN 174/X Trimulya. Data was collected using observation techniques, questionnaires and written tests. Data analysis uses quantitative descriptive analysis. The results of the research prove that the application of the Problem Based Learning model can improve the learning outcomes of class IV students in the science and science subject on Cultural Diversity in Indonesia. The average observation results of student learning outcomes in cycle I was 87.52%, in cycle II it increased to 90.00%, the results of the questionnaire. Student learning outcomes obtained an average of 60.55% in cycle I and in cycle II it increased to 89.31%.